Bacterial Vaginosis and Its Association With Incident Trichomonas vaginalis Infections: A Systematic Review and Meta-Analysis. Issue 12 (25th December 2021) - Seña, Arlene C.; Goldstein, Linda A.; Ramirez, Gilbert; Parish, Austin J.; McClelland, R. Scott
Abstract : This systematic review and meta-analysis provide support for a nearly 2-fold higher risk for acquiring Trichomonas vaginalis among women with bacterial vaginosis compared with women without bacterial vaginosis. Supplemental digital content is available in the text. Abstract : Background: Bacterial vaginosis (BV) has been associated with an increased risk for acquisition of human immunodeficiency virus and sexually transmitted infections. We evaluated the association between BV and incident Trichomonas vaginalis (TV) infection in women. Methods: MEDLINE and ClinicalTrials.gov were searched for articles published between January 1, 1980, and May 7, 2021. Observational studies in women that evaluated the relationship between having/not having BV and the risk for acquiring TV were included. Results: Fourteen studies were included in the systematic review; 12 studies were included in meta-analyses involving 18, 424 participants. Most studies used Nugent scoring to diagnose BV. For TV diagnosis, 12 studies used wet mount microscopy or culture, and 2 used nucleic acid amplification tests. There was diversity in the measures of association used, so an overall effect size could not be calculated. The majority of studies reported odds ratios, which showed an increased risk of incident TV among women with BV versus without BV (adjusted odds ratio, 1.87; 95% confidence interval, 1.45–2.40; P = 0.007). However, there were heterogeneity and potential confounding factors (eg, age, sexual partners) reported among studies. Conclusions: This systematic review and meta-analysis provide evidence for a nearly 2-fold higher risk for acquiring TV among women with BV compared with women without BV.